2019
DOI: 10.1111/bcpt.13201
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin inhibits panel of kinases implicated in tumorigenesis

Abstract: Myricetin is a flavonoid with several biological properties, including antioxidant and anti‐inflammatory features. Its protective effect in chronic diseases may occur through the inhibition of protein kinases that trigger inflammation and carcinogenesis pathways. Considering the influence of kinases on such pathological disorders, it is crucial to study compounds that inhibit these proteins. This study aims to evaluate the inhibitory potential of 14 flavonoids on TNF‐α release in human whole blood as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…36,37,40 Myricetin has also been reported as an inhibitor against multiple kinases implicated in tumorigenesis. 41 Furthermore, hyperoside was identified as an effective inhibitor of human cytochrome P450 2D6 (CYP2D6) with an IC 50 of 1.2 μM. 42 Our cocrystal structure showed that myricetin allosterically inhibited RNase L activity by binding to the ATP pocket, which is similar to sunitinib as characterized in our previous study.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 64%
See 1 more Smart Citation
“…36,37,40 Myricetin has also been reported as an inhibitor against multiple kinases implicated in tumorigenesis. 41 Furthermore, hyperoside was identified as an effective inhibitor of human cytochrome P450 2D6 (CYP2D6) with an IC 50 of 1.2 μM. 42 Our cocrystal structure showed that myricetin allosterically inhibited RNase L activity by binding to the ATP pocket, which is similar to sunitinib as characterized in our previous study.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 64%
“…Hyperoside is often isolated from various medicinal plants, for example Hypericum perforatum and Crataegus davisii . Many pharmacological studies reported that myricetin, vitexin, and hyperoside can be used in anti-inflammatory responses and cardioprotective, antiviral, and antitumor treatments. ,, Myricetin has also been reported as an inhibitor against multiple kinases implicated in tumorigenesis . Furthermore, hyperoside was identified as an effective inhibitor of human cytochrome P450 2D6 (CYP2D6) with an IC 50 of 1.2 μM …”
Section: Discussionmentioning
confidence: 99%
“…Myricetin is found in a variety of fruits and vegetables, nutrient‐enriched foods, especially grapes, and berries used in winemaking (Wang et al, 2019). Some studies reported that myricetin has antihypertensive and antitumor effects (Godse et al, 2010; Jiang et al, 2019; Stoll et al, 2019). Cetin‐Karaca & Newman (2015) found that myricetin showed significant antimicrobial activity against Escherichia coli , Salmonella paratyphi , Salmonella enterica , and Salmonella enteritidis .…”
Section: Resultsmentioning
confidence: 99%
“…Myricetin is found in a variety of fruits and vegetables, nutrient-enriched foods, especially grapes, and berries used in winemaking (Wang et al, 2019). Some studies reported that myricetin has antihypertensive and antitumor effects (Godse et al, 2010;Jiang et al, 2019;Stoll et al, 2019).…”
Section: The Major Phenolic Components Of Kefir Samples Containingmentioning
confidence: 99%
“…56 Its protective effects in chronic diseases may be achieved by inhibiting inflammation-triggering and related protein kinases with the potential to treat COPD. 57 In emphysema models, ellagic acid, as a natural antioxidant, has a protective effect against pulmonary hypertension and the development of lung and heart damage induced by elastase. 58 Luteolin, a natural flavonoid, can treat COPD by altering the M1/M2 polarization of macrophages, thereby exerting anti-inflammatory effects through downregulation of p-STAT3 and upregulation of p-STAT6, 59 as well as through ERK-mediated inflammation, apoptosis, and autophagy inhibition.…”
Section: Discussionmentioning
confidence: 99%